Revolution of Islamic Education Thought in the Era of Society 5.0: Correction and Review of Field Studies - Mudhiah; Shapiah; Suraijiah; Rusdiah (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This research aims to explore the revolution of Islamic education thinking in the era of Society 5.0 with a focus on the integration of religious values with technology at UIN Antasari Banjarmasin. The research method used is qualitative with in-depth interviews with lecturers and direct observation of teaching practices on campus. The results showed that lecturers at UIN Antasari Banjarmasin are actively involved in efforts to integrate religious values with technology-based teaching methods, creating an educational environment that is responsive to the demands of the Society 5.0 era. This research provides a scientific contribution by confirming the importance of this integration in shaping a balanced and relevant Islamic education during rapid technological development. However, there are limitations to the study, including limited generalizability and the need for further research with a quantitative approach to gain a more in-depth and comprehensive understanding. Future research could involve a wider sample and contextual variations to test the validity of the findings. In addition, a quantitative approach could provide a more robust statistical analysis to support the qualitative findings. Thus, the results of this study provide a basis for further development in exploring the role of integrating religious values with technology in improving the quality of Islamic education in the era of Society 5.0.